TAKEMITSU TŌRU AND HIS MUSIC – IS IT REALLY JAPANESE (AFTER ALL)? - Wolniak, Małgorzata (Porównania, 2016)
Takemitsu Toru is one of the most prominent and recognizable Japanese contemporary composers. The composer is famous for his skill of combining the elements of traditional Japanese music with Western style composition. The article presents his career, inspirations, Japanese aesthetics such as ma and sawari. His perception of music and his relation to Japanese music and traditional instruments in comparison to the Western music traditions is also described.